Identifying and Treating Vulnerable Atherosclerotic Plaques - Ambrose, John A.; Sharma, Avinash V. (The American journal of cardiology, 2023)
Acute coronary syndromes and, in particular, ST-elevation myocardial infarction are usually caused by coronary thrombosis in which the thrombus develops either on a disrupted plaque (usually a thin-capped fibroatheroma) or an eroded atherosclerotic plaque. These thrombus-prone plaques are vulnerable or high-risk. Although, traditionally, cardiologists have concentrated on treating significant coronary obstruction, there has been great interest over the last 2 decades in possibly preventing the thrombotic causes of myocardial infarction/sudden coronary death by mostly identifying and stabilizing these asymptomatic vulnerable or high-risk plaques, which, at least on invasive angiography, are mostly nonobstructive. Computed tomographic angiography and intravascular imaging during invasive coronary angiography have now been shown to identify a majority of these vulnerable or high-risk plaques before symptoms, thus opening up new preventive strategies. In conclusion, this article discusses the identification and management of these thrombus-prone lesions and patients with these lesions either with noninvasive techniques and systemic therapies or possibly through a new and bold interventional paradigm.